2018
DOI: 10.1186/s13756-018-0316-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and successful management of a respiratory syncytial virus outbreak among pediatric patients with hemato-oncological disease

Abstract: BackgroundRespiratory syncytial virus (RSV) is responsible for upper and lower respiratory tract infection in adults and children. Especially immunocompromised patients are at high risk for a severe course of infection, and mortality is increased. Moreover RSV can spread in healthcare settings and can cause outbreaks. Herein we demonstrate the successful control and characteristics of a RSV outbreak that included 8 patients in our Department of Pediatric Hematology and Oncology.MethodsWe performed an epidemiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Finally, a recent study conducted in special high-risk settings such as hematology and oncology units, suggests that the diagnoses of asymptomatic virus infections, such as RSV and influenza, can be useful to lower the risk of hospital acquisition. The screening program proved useful for identifying asymptomatically infected patients with viral shedding, thus reducing the risk of transmission and potential nosocomial clusters of RSV and influenza virus on hemato-oncological wards (Baier et al, 2018).…”
Section: Can Multiplex Platforms Reduce the Medical And Socioeconomicmentioning
confidence: 99%
“…Finally, a recent study conducted in special high-risk settings such as hematology and oncology units, suggests that the diagnoses of asymptomatic virus infections, such as RSV and influenza, can be useful to lower the risk of hospital acquisition. The screening program proved useful for identifying asymptomatically infected patients with viral shedding, thus reducing the risk of transmission and potential nosocomial clusters of RSV and influenza virus on hemato-oncological wards (Baier et al, 2018).…”
Section: Can Multiplex Platforms Reduce the Medical And Socioeconomicmentioning
confidence: 99%
“…Some practice-leading hospitals were also screening, and in some cases testing, all admissions for influenza and RSV during respiratory virus season, even before the current SARS-CoV-2 pandemic demonstrated the importance and potential benefits of admission screening. 44 80 A cluster randomized trial of point-of-care admission testing for influenza found that point-of-care admission testing was associated with higher rates of influenza diagnosis, more use of antiviral treatment, less time to initiation of antivirals, and almost double the rate of isolating influenza-positive patients in single patient rooms. 81 Another study associated the introduction of rapid early influenza tests for selected patients with a 75% decrease in hospital-acquired influenza cases.…”
Section: Symptom Screening and Universal Testingmentioning
confidence: 99%
“…Za preprečevanje prenosa okužbe bi bilo otrokom z okužbo zgornjih dihalnih poti smiselno omejiti gibanje zgolj na domače okolje, vendar pa lahko to povzroči tudi socialno osamljenost (Baier et al, 2018). Tudi v času epidemije koronavirusne bolezni so bili otroci izpostavljeni socialni izolaciji, kar se kaže na njihovem duševnem zdravju.…”
Section: Raven Dokaza / Level Of Evidenceunclassified